Pengenalan Materi Jaringan Komputer di SD Negeri Purwosari - Tsaqif Taqiyulloh Jabar Ro’uf; Muhammad Bintang Ramadhan; Vadaros Ahirozon; Firdaus Purwantoro (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to introduce the basic concept of computer networks to the students of SD Purwosari. In today's digital era, a basic understanding of computer networks is crucial to equip the younger generation with adequate technological literacy. The implementation method involves interactive socialization, simple demonstrations, and hands-on practice. The results of the activity showed an increase in students' understanding of basic concepts such as the internet, Wi-Fi, and network devices. The outputs achieved include simple teaching modules and increased student enthusiasm for technology. The conclusion of this activity is that the introduction of computer network material at an early age is very important and can be done with methods that are appropriate to the level of understanding of children.